Personal information from Bangla speech signal using MFCC and GMM - Hridy, Maisha Munawara; Hasan, Md. Hasib; Emon, Mahfuz Al (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.